Metabolism and disposition in rats, dogs, and humans of erdafitinib, an orally administered potent pan-fibroblast growth factor receptor (FGFR) tyrosine kinase inhibitor. (1st February 2021) - Scheers, Ellen; Borgmans, Carine; Keung, Chi; Bohets, Hilde; Wynant, Inneke; Poggesi, Italo; Cuyckens, Filip; Leclercq, Laurent; Mamidi, Rao N. V. S.
Abstract: This article describes in vivo biotransformation and disposition of erdafitinib following single oral dose of 3 H-erdafitinib and 14 C-erdafitinib to intact and bile duct-cannulated (BC) rats (4 mg/kg), 3 H-erdafitinib to intact dogs (0.25 mg/kg), and 14 C-erdafitinib to humans (12 mg; NCT02692677). Peak plasma concentrations of total radioactivity were achieved rapidly ( T max : animals, 1 h; humans, 2–3 h). Recovery of drug-derived radioactivity was significantly slower in humans (87%, 384 h) versus animals (rats: 91–98%, 48 h; dogs: 81%, 72 h). Faeces was the primary route of elimination in intact rats (95%), dogs (76%), and humans (69%); and bile in BC rats (48%). Renal elimination of radioactivity was relatively low in animals (2–12%) versus humans (19%). Unchanged erdafitinib was major component in human excreta (faeces, 17%; urine, 11%) relative to animals. M6 (O-desmethyl) was the major faecal metabolite in humans (24%) and rats (intact, 46%; BC, 11%), and M2 (O-glucuronide of M6) was the prevalent biliary metabolite in rats (14%). In dogs, besides M6, majority of radioactive dose in faeces was composed of multiple minor metabolites. In humans, unchanged erdafitinib was the major circulating entity. O-demethylation of erdafitinib was the major metabolic pathway in humans and animals.